2023
DOI: 10.3389/fpubh.2023.1186307
|View full text |Cite
|
Sign up to set email alerts
|

Using participatory action research to empower district hospital staff to deliver quality-assured essential surgery to rural populations in Malawi, Zambia, and Tanzania

Chiara Pittalis,
Grace Drury,
Gerald Mwapasa
et al.

Abstract: BackgroundIn 2017 the SURG-Africa project set out to institute a surgical, obstetric, trauma and anesthesia (SOTA) care capacity-building intervention focused on non-specialist providers at district hospitals in Zambia, Malawi and Tanzania. The aim was to scale up quality-assured SOTA care for rural populations. This paper reports the process of developing the intervention and our experience of initial implementation, using a participatory approach.MethodsParticipatory Action Research workshops were held in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 34 publications
1
2
0
Order By: Relevance
“…The perception of the participants that BRIDGE action research activities provide a good platform for learning, bridges disciplinary gaps and puts a focus on the practical issues affecting the participants is consistent with reported findings from applying an action research approach to development projects in sub-Saharan Africa (Wood and Govender 2013;Niyobuhungiro and Schenck 2022;Pittalis et al 2023). Wood and Govender (2013) observed that there is learning through the action research process, as already discussed above.…”
Section: Perception Of Action Research Approach By the Participantssupporting
confidence: 83%
See 1 more Smart Citation
“…The perception of the participants that BRIDGE action research activities provide a good platform for learning, bridges disciplinary gaps and puts a focus on the practical issues affecting the participants is consistent with reported findings from applying an action research approach to development projects in sub-Saharan Africa (Wood and Govender 2013;Niyobuhungiro and Schenck 2022;Pittalis et al 2023). Wood and Govender (2013) observed that there is learning through the action research process, as already discussed above.…”
Section: Perception Of Action Research Approach By the Participantssupporting
confidence: 83%
“…Wood and Govender (2013) observed that there is learning through the action research process, as already discussed above. According to Pittalis et al (2023), feedback from the action research participants based on their perception could provide support for the design of a locally relevant and contextualized intervention. In addition, this can contribute to co-development of knowledge, which requires collaboration of different groups of stakeholders, and this gives voice to the concerned communities on issues that affect them.…”
Section: Perception Of Action Research Approach By the Participantsmentioning
confidence: 99%
“…13 We also published a paper demonstrating the successful participatory research model for collaboration in three African countries between a wide range of incountry stakeholders, local ministries of health and other regulatory bodies, as part of the international SURG-Africa research consortium. 14…”
Section: W E Welcome the Commentaries Published By The International ...mentioning
confidence: 99%